Copper(I) Thiocyanate (CuSCN) Hole‐Transport Layers Processed from Aqueous Precursor Solutions and Their Application in Thin‐Film Transistors and Highly Efficient Organic and Organometal Halide Perovskite Solar Cells. (28th July 2017) - Wijeyasinghe, Nilushi; Regoutz, Anna; Eisner, Flurin; Du, Tian; Tsetseris, Leonidas; Lin, Yen‐Hung; Faber, Hendrik; Pattanasattayavong, Pichaya; Li, Jinhua; Yan, Feng; McLachlan, Martyn A.; Payne, David J.; et al.
Abstract : This study reports the development of copper(I) thiocyanate (CuSCN) hole‐transport layers (HTLs) processed from aqueous ammonia as a novel alternative to conventional n‐alkyl sulfide solvents. Wide bandgap (3.4–3.9 eV) and ultrathin (3–5 nm) layers of CuSCN are formed when the aqueous CuSCN–ammine complex solution is spin‐cast in air and annealed at 100 °C. X‐ray photoelectron spectroscopy confirms the high compositional purity of the formed CuSCN layers, while the high‐resolution valence band spectra agree with first‐principles calculations. Study of the hole‐transport properties using field‐effect transistor measurements reveals that the aqueous‐processed CuSCN layers exhibit a fivefold higher hole mobility than films processed from diethyl sulfide solutions with the maximum values approaching 0.1 cm 2 V −1 s −1 . A further interesting characteristic is the low surface roughness of the resulting CuSCN layers, which in the case of solar cells helps to planarize the indium tin oxide anode. Organic bulk heterojunction and planar organometal halide perovskite solar cells based on aqueous‐processed CuSCN HTLs yield power conversion efficiency of 10.7% and 17.5%, respectively. Importantly, aqueous‐processed CuSCN‐based cells consistently outperform devices based on poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate HTLs. This is the first report on CuSCN films and devices processed via an aqueous‐based synthetic route that is compatible with high‐throughput manufacturing and paves the way for further developments. Abstract : Dissolution of copper thiocyanate (CuSCN) in aqueous ammonia enables processing of superior quality hole‐transporting layers at low temperature in ambient air. Transistors based on these CuSCN layers exhibit mobilities close to 0.1 cm 2 V −1 s −1, while solar cells incorporating CuSCN interlayers yield power conversion efficiencies of 10.7% and 17.5% for organic bulk heterojunction and organometal halide cells, respectively.